2012
DOI: 10.7314/apjcp.2012.13.5.2315
|View full text |Cite
|
Sign up to set email alerts
|

Use of Smoke-less Tobacco Amongst the Staff of Tertiary Care Hospitals in the Largest City of Pakistan

Abstract: Background: Use of smoke-less tobacco (SLT) is very common in South and South-East Asian countries. It is significantly associated with various types of cancers. The objectives of this study were to assess the proportion of hospital staff that use SLT, and to identify the factors associated with its use and their practices. Methods: In a cross-sectional study, 560 staff of two tertiary care hospitals were interviewed in the year 2009. Nurses, ward boys and technicians were counted as a paramedic staff while dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Use of smoke-less tobacco (SLT) is very common in South and South-East Asian countries (Valliani et al, 2012). Shammah is used in KSA and Yemen.…”
Section: Different Types Of Smokeless Tobaccomentioning
confidence: 99%
See 1 more Smart Citation
“…Use of smoke-less tobacco (SLT) is very common in South and South-East Asian countries (Valliani et al, 2012). Shammah is used in KSA and Yemen.…”
Section: Different Types Of Smokeless Tobaccomentioning
confidence: 99%
“…The study showed that a high percentage of paramedical staff of public sector hospitals consume ST in different forms. Most common type consumed is 'Gutka' and their family or friends influenced approximately half of them (Valliani et al, 2012). A relatively high prevalence of smokeless tobacco consumption among the male students of universities of Zahedan, Iran (Honarmand et al, 2013).…”
Section: Different Types Of Smokeless Tobaccomentioning
confidence: 99%
“…The increasing risk factor includes; poor sanitary conditions, overpopulation, consumption of raw foods, like food items purchased from street stalls and unsafe water supply sources (Zhong et al, 2012). Smoking and smokeless tobacco use are associated with increasing risk of H. pylori, which is very common in south Asian countries, mainly Pakistan (Wu et al, 2003;Valliani et al, 2012). Some studies reported that alcohol is protected against infection while coffee had the opposite effect, but these results are variable (Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…By avoiding this habit, risk of this illness can be minimized [4]. For control and prevention of pathogenic bacteria from spreading, food and water should be treated in such a way that there would be no or minimum chances of contamination [60].…”
Section: Control and Prevention Of Gastroenteritismentioning
confidence: 99%
“…From 2008 to 2015, one million deaths have been recorded in Pakistan alone which reflects the severity and primarily significance of this notorious infection [2]. Outbreaks of gastroenteritis primarily depends upon a variety of risk factors among children and adults such as contaminated pond water which was used for washing, bathing, drinking and cooking purposes without boiling [3], use of smokeless tobacco [4], malnutrition, excessive use of antibiotics as well as psychological factors such as anxiety, depression [5] and immunocompromised patients [6].…”
Section: Introductionmentioning
confidence: 99%